1317 A QUALITY IMPROVEMENT PROJECT AIMING TO ENHANCE THE RECOGNITION OF INPATIENT WEIGHT LOSS ON AN ELDERLY WARD. (16th January 2023) - Large, O; Melrose, R; Babatunde, A; Thomson, F; Stapley, S
Abstract: Background: Weight loss in the older adult is often multifactorial and can be associated with increased morbidity and mortality. Our quality improvement project focused on nutritional care of patients 75 years or older. This hospital has a standardised Nutrition and Hydration Policy based on NICE guidelines to prevent malnutrition in hospital inpatients including weighing patients every 72 hours, daily screening and food/hydration charts. Our project aimed to increase adherence, with a focus on increasing the percentage of patients being regularly weighed over a 6-month period to 90%. Methods: Our stakeholder analysis highlighted the multidisciplinary nature of our project, particularly involving the healthcare assistants. The percentage of patients weighed within 72 hours was recorded weekly. The first PDSA cycle introduced the project and gained buy-in from the MDT, highlighting required weights in MDT meetings/board rounds. The second cycle included an education session for doctors. The third cycle involved a poster in each bay aiming to act as a prompt and promote patient and family involvement. Results: Our run chart shows that following our first two PDSA cycles eight consecutive results were higher than the baseline (40% of patients weighed). Results ranged from 70-90%. Following the third intervention compliance returned to baseline but coincided with significant disruption to the ward structure and team. Our successful intervention of nutritional teaching was then repeated as a fourth PDSA cycle and the mean returned to 80%. Conclusions: Nutritional care requires multidisciplinary involvement. The educational session had the most impact and in future could be delivered to additional MDT members. Disappointingly the poster did not stimulate patient or family participation. We would like to create an ethos on elderly wards where nutrition routinely features in ward-based comprehensive geriatric assessments. Future plans hope to further engage patients and families as visiting restrictions eased.